Faktor yang Berhubungan dengan Praktik Manajemen Terpadu Bayi Muda oleh Gasurkes KIA di Kota Semarang - Sinta Wati; Apoina Kartini; Martini Martini; Ayun Sriatmi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: The main causes of neonatal deaths in Semarang city were low birth weight (LBW) approximately 38%, birth asphyxia (23%), congenital defect (8%), infections such as sepsis (3%), jaundice (3%), and others (25%). The most common causes of mortality were considered preventable and treatable at an affordable, easily-to-implement, and efficient through integrated management of young infants (IMYI) performed during neonatal visits. It has previously been observed that IMYI has contributed to reducing the neonatal mortality rate by 30-60%. This study aims to investigate the factors that determine the integrated management of young infants carried by maternal and perinatal death surveillance and response (MPDSR) workers in Semarang city.Methods: Quantitative research designs were adopted to provide the correlation between independent variables and dependent variables using statistical hypothesis testing. A cross-sectional approach was utilized to collect the data, both independent dan dependent variables simultaneously. The data were analyzed using chi-square, Fisher exact test, and logistic regression.Results: The result suggests that knowledge, work period, attitude, workload, recording system, supervision had an association toward the practice of IMYI conducted by MPDSR workers in Semarang City. No significant correlation was found on the availability of tools and appraisal toward the practice of IMYI. Work periods was the most dominant factor affecting IMYI practice.Conclusion: these results indicate that knowledge, work period, attitude, workload, recording system, supervision has an important role to increase the practice of IMYI performed by maternal and perinatal death surveillance and response (MPDSR) workers in Semarang city.